The Relationship of Health Education to Knowledge Elderly about Prevention Hypertension in Posyandu Elderly Nagori Dusun Ulu, Ujung Padang District - Doortua; Laia, Ratna Juwita (PT Inovasi Pratama Internasional, 2023)
Hypertension Still become problem health in groups elderly. Enhancement age often followed disease degenerative and problematic health in groups carry on age For That researcher interested do research entitled connection education health to knowledge elderly about method prevention hypertension in posyandu elderly Nagori Dusun Ulu, Ujung Padang District, Regency Simalungun 2022. Research this conducted in July -September 2022 with population as many as 198 people meanwhile sample used as many as 99 people with use formula from book Lemeshow with use technique simple random sampling. Research results this state that education health have connection to knowledge elderly in posyandu elderly Nagori Dusun Ulu, Ujung Padang District, Regency Simalungun In 2022, because the p value « 0.05. Expected can done upgrade knowledge cadres Integrated Healthcare Center elderly about hypertension and ways prevention as well as increase ability cadre in give counseling so that counseling to elderly more effective. educational institutions provide material Integrated Healthcare Center seniors who are one service health base through eye related courses with service Iansia Good integrally as well in a manner special case hypertension in the elderly and how prevention. Research results This as initial data for do study other about elderly with different variables.